(untitled) (Iraqi Journal of Medical Sciences, 2023)
Background: Acne vulgaris is a chronic skin disease caused by many factors includes: hormonal disturbance, increase sebum production and inflammatory skin due to multi-drug resistant (MDR) bacteria Staphylococcus aureus (S. aureus). So, there is an urgent need for bacteriophages (Elixir of life) as an alternative strategy to reduce the overuse of antibiotics and combat MDR bacterial pathogens. Objective: To develop a bacteriophage cocktail specific for MDR S. aureus bacteria and investigates its efficacy via in vitro validation tests and in vivo topical applied on human skin acne lesions caused by MDR bacterial infections. Methods: Twenty-three bacteriological isolates of S. aureus were collected from patients at 20-40 years old with acne lesions that admitted to Al-Yarmouk Teaching Hospital, Baghdad, Iraq. Then, identified and susceptibility tests performed via VITEK2 system. Bacteriophages were isolated from sewage water, then bacteriophages cocktail prepared and determined their lytic activity via in vitro validation tests and investigate their clinical efficacy on the skin of human with acne lesions caused by MDR S. aureus bacteria. Results: The bacteriophage cocktail therapy with high antibacterial lytic activity via in vitro validation tests proved excellent effectiveness in treating patients from MDR S. aureus acne vulgaris via clinical improvement in size, number, inflammatory signs of acne lesions, and decolonization of MDR S. aureus bacteria in treated lesions as compared with untreated, control lesions. Conclusion: Bacteriophage cocktail specific for S. aureus bacteria can be prepared in laboratory with simple measures, and safe without any side effect on human patients whom topically applied it. Keywords: Bacteriophage, cocktail, MDR, S. aureus bacteria, clinical investigate Citation: Hussain HE, Abdulamir AS, Farhood IG, Abu Raghif AR, Ali MR. Clinical investigation of the bacteriophage cocktail efficacy on acne vulgaris caused by multi-drug resistance Staphylococcus aureus. Iraqi JMS. 2023; 21(2): 208-223. doi: 10.22578/IJMS.21.2.9